2022
DOI: 10.1038/s41598-022-14904-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue volume estimation and age prediction using rapid structural brain scans

Abstract: The multicontrast EPImix sequence generates six contrasts, including a T1-weighted scan, in ~1 min. EPImix shows comparable diagnostic performance to conventional scans under qualitative clinical evaluation, and similarities in simple quantitative measures including contrast intensity. However, EPImix scans have not yet been compared to standard MRI scans using established quantitative measures. In this study, we compared conventional and EPImix-derived T1-weighted scans of 64 healthy participants using tissue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies on EPIMix in adult patients have investigated a variety of neurological conditions, such as ischemic stroke [ 10 , 11 ], patients with suspicion of brain pathology [ 8 ], and the clinical feasibility of the sequence [ 9 , 24 ]. These studies showed comparable diagnostic performance [ 8 , 10 , 11 ] and sufficient image quality [ 9 ] for EPIMix compared to routine brain MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on EPIMix in adult patients have investigated a variety of neurological conditions, such as ischemic stroke [ 10 , 11 ], patients with suspicion of brain pathology [ 8 ], and the clinical feasibility of the sequence [ 9 , 24 ]. These studies showed comparable diagnostic performance [ 8 , 10 , 11 ] and sufficient image quality [ 9 ] for EPIMix compared to routine brain MRI.…”
Section: Discussionmentioning
confidence: 99%